PENGARUH KECERDASAN EMOSIONAL DAN DUKUNGAN SOSIAL TERHADAP SUBJECTIVE WELL-BEING SERTA PERAN HARDINESS SEBAGAI VARIABEL MEDIASI (Pada Pegawai Dinas Perhubungan Kota Pasuruan) - Rachmadi Setyawan; Muchlis Mas’ud; Survival, Survival (Bajang Institute, 2025)
This study aims to test and analyze the influence of emotional intelligence and social support on subjective well-being and the role of hardiness as a mediating variable. The population in this study were all employees of the Pasuruan City Transportation Agency, totaling 53 employees. The sampling technique in this study was total sampling. The data analysis technique used in this study was Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS software version 4.0. The results showed that better emotional intelligence was able to encourage an increase in subjective well-being. Better emotional intelligence was able to encourage an increase in hardiness. Although social support was getting stronger, it was not able to encourage an increase in subjective well-being. Better social support was able to encourage an increase in hardiness. Better hardiness was able to encourage an increase in subjective well-being. Emotional intelligence significantly influenced subjective well-being with Hardiness as a partial mediating variable. Social support significantly influenced subjective well- being with Hardiness as a perfect mediating variable